2017
DOI: 10.1111/jpn.12660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa oleifera silage on milk yield, nutrient digestibility and serum biochemical indexes of lactating dairy cows

Abstract: SummaryThis study investigated the effects of Moringa oleifera (MO) as a partial substitute of alfalfa hay on milk yield, nutrient apparent digestibility and serum biochemical indexes of dairy cows. MO was harvested at 120 days post-seeding. Fresh MO was cut, mixed with chopped oat hay (425:575 on a DM basis), ensiled and stored for 60 days. Sixty healthy Holstein dairy cows were allocated to one of three groups: NM (no MO or control), LM (low MO; 25% alfalfa hay and 50% maize silage were replaced by MO silage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
(32 reference statements)
7
18
0
Order By: Relevance
“…Their differences were significant ( p < 0.05). These results confirm the previous findings [ 10 , 11 , 23 , 26 , 27 ] that moringa foliage is a good source of protein-rich amino acids that can enhance the utilization of dietary N and can boost the production and productivity of the dairy animal.…”
Section: Discussionsupporting
confidence: 92%
“…Their differences were significant ( p < 0.05). These results confirm the previous findings [ 10 , 11 , 23 , 26 , 27 ] that moringa foliage is a good source of protein-rich amino acids that can enhance the utilization of dietary N and can boost the production and productivity of the dairy animal.…”
Section: Discussionsupporting
confidence: 92%
“…Coincidentally, (95) found that cow diets with 20 and 40% M. oleifera resulted in 25 and 16% increase in daily milk yield and higher levels of nutrients in milk as compared with those in Trifolium alexandrium hay diet. In addition, (96) noted that M. oleifera leaf meal completely replaced maize silage in lactating dairy cows diet but did not affect dry matter intake, milk yield, or milk composition. However, cows fed with over 50% M. oleifera leaf meal showed low serum concentrations of total cholesterol, high-density lipoprotein cholesterol, and lowdensity lipoprotein cholesterol and higher serum concentrations of urea than the control group.…”
Section: Effects Of M Oleifera Leaves On Ruminant Performancementioning
confidence: 97%
“…Dry matter intake (DMI) was calculated based on the DM content in feed provided and daily ort measurements. The cows were fed individually, and the DMI of each cow was measured as feed offered and refused to calculate the average daily DMI per cow [14]. Over the last 3 d of the experiment, fecal samples (about 300 g) were obtained by stimulating the rectum to cause emissions at 02:00, 08:00, 14:00, and 20:00 h on day 58; at 00:00, 06:00, 12:00, and 18:00 h on day 59; and at 22:00, 04:00, 10:00, and 16:00 h on day 60 [15].…”
Section: Sample Collectionmentioning
confidence: 99%